Evaluation of Landscape Design Procedure ; A Case Study from Ispir Erzurum Social Facility Complex - Sevgi Yılmaz; Murat Çınar (Journal of Agricultural Sciences)
The main goal of landscape design studies is to construct more comfortable living areas for human beings by arranging natural and socio-cultural factors. The Ispir Social Facility complex, an environmental arrangement project, was evaluated for its physical atmosphere, comfort and aesthetic satisfaction. The Landscape Gardening Project study comprising 8950 square metres in the area was achieved through putting forward the subject /matter, data collection on the present situation, expasing the final product design , making analysis, development, evaluation and synthesis in collaboration with local administration.